Commentary: Are You Experienced? (LEARNing Landscapes, 2014)
Educational experience, I suggest, depends on having embodied experience from which one can learn. What can one learn from virtual experience? One can acquire information online, but can one craft that personal practical knowledge that derives from being experienced? That ongoing project requires that information be worked through—idiosyncratically—incorporating the new into one’s prior knowledge and emotional-intellectual gestalt, thereby cultivating the capacity for (situation-specific) judgment. Despite policymakers’ insistence that technology structure almost every classroom experience, many educators appreciate that their subjective presence is prerequisite to social learning. These facts and convictions inform this brief commentary on "experience."
Keywords: experience; online; technology; social; learning